In-Vivo Anti-Inflammatory Activity of Kelubut Leaf Ethyl Acetate Extract (Passiflora foetida L.) from Samarinda City - Mochtar, Chaerul Fadly; Devi, Reni Selviana; Hamzah, Hasyrul; Faradillah, Ayu; Hafidzah, Elva; Varizza, Fathiah Putri; Aisyiyah, Novia Misnawati; Husna, Qur'anni Akhwatun (Journal of Fundamental and Applied Pharmaceutical Science, 2023)
Kelubut (Passiflora foetida L.), as an anti-inflammatory, is widely found in various regions in Indonesia, including in Central Kalimantan. Its main chemical compounds include alkaloids, phenols, glycosides, flavonoids, and cyanogenic compounds. Flavonoids show more than a hundred kinds of bioactivity, including antipyretic, analgesic, and anti-inflammatory. This study aims to determine the anti-inflammatory activity of kelubut leaf extract (Passiflora foetda L.) against mice (Mus musculus). This research went through a Pretest and Posttest Control Group Design with 5 treatment groups, negative control, positive control, and ethyl acetate extract of kelubut leaves with 3 doses of 250 mg/KgBW, 125mg/KgBW and 62.5 mg/KgBB. Before being given treatment, each treatment group was induced by carrageenin by sub-planar injection into the sole of the left leg of the mouse. Then, the edema developed rapidly and persisted for 6 hours. After being induced by carrageenin, the researchers waited for 30 minutes and measured the volume of edema every 30 minutes to 120 minutes. The inhibition of all groups of ethyl acetate extract of kelubut leaves showed anti-inflammatory activity, but the resulting abilities were different. Inflammation inhibition by ethyl acetate extract at a dose of 250 mg/KgBW was 92.78%, at a dose of  125 mg/KgBW, was 91.76%, and at a dose of 62.5 mg/KgBW was 84.61%. From the results obtained, the ethyl acetate extract group of kelubut leaves at a dose of 250 mg/KgBW had the greatest inflammatory inhibition activity compared to a dose of 125 mg/KgBW and 62.5 mg/KgBW.